Strict Liability Pada Kebakaran Hutan Dalam Perspektif Undang-Undang Nomor 32 Tahun 2009 - Defril Hidayat Defril; Arzam Arzam; Ayu Efritadewi (Jurnal Selat, 2021)
Forest fires are a form of environmental damage, this occurs due to illegal burning or due to human treatment, therefore forest areas need attention. Recovery of the situation as a result of environmental pollution, the government forms a responsibility that is imposed on actors or businesses that can cause environmental pollution, this is called strict liability as stated in Law no. 32 Year 2009 About the Environment. This research uses normative law research methods. The purpose of this study is to find out how strict liability in forest conservation is regulated in a law. Article 88 of the Law on the Environment, explains that the concept of absolute responsibility is imposed on the perpetrator whose actions or efforts cause environmental pollution without having to prove an element of guilt, which means that the concept of the environment in the case of forest fires is to restore environmental conditions, not to take action. punish the perpetrator first. This study concludes that the concept of Strict Liability has been properly regulated in the UUPLH to restore a polluted environment and in the case of forest fires the concept of Strict Liability mandated by UUPLH has not been implemented considering the need for rapid environmental recovery, therefore the government acts as the person in charge which is not mandated by UUPLH. but this denial has a good purpose to protect the community from environmental pollution due to smog.